Glaucoma Basic and Clinical Aspects - Rumelt, Shimon (IntechOpen, 2013)
Glaucoma is a specialty in ophthalmology that includes a group of diseases that affect the optic disc and visual fields and is usually accompanied by increased intraocular pressure. This book addresses new topics in glaucoma that have not been included and expands topics that have been included in the previous glaucoma books published by InTech. The book is a product of balance between expedited publication and the will to encompass the whole field and therefore contains the latest developments and new perspectives in glaucoma. It is intended for glaucoma specialists, general ophthalmologists, trainees and researches to increase the knowledge and understanding these complex diseases and to encourage further investigation for the benefit of the entire human community.